Dynamics of fiscal and current account deficits in Thailand : an empirical investigation - Ahmad Zubaidi, Baharumshah; Lau, Evan (Emerald Group Publishing Limited, 2007)
Purpose – The purpose of this paper is to contribute further on the twin deficits debate in a developing economy.